Assessment of students' knowledge regarding breast self-examination in Erbil City-Iraq - azez, Kareem; Sheren, nazar (Iraqi National Journal of Nursing Specialties, 2011)
Breast cancer is the most common cause of death among women worldwide (1). Breast self-exam (BSE) is consideredan important public health procedure; primary prevention should be given the highest priority in the fight againstcancer.Cancer is considered the second leading cause of death in developed countries there was some 6.2 million cancerrelated deaths, accounƟng for 12% of all deaths globally (5).Patients perception toward this disease and preferenceconcerning the types and aims of their treatment are vary they may loss hopes and become devastated and crippledor even dies earlier, if told about the diagnosis (13). The study aimed to assess knowledge of female students regardingBSE, and to find out relationship between sociodemographic variables and breast self-exam.One hundred of female students from, Medical technical institute in the first and second class were selected toparticipate in the study. The questionnaire was designed for data collection. The data were collection from January 1st,2010 to March 20th, 2010.The questionnaire it consists of two parts related to sociodemoraphic characteristics for study sample, and femalestudent's knowledge about breast self exam. The study revealed that female student's knowledge about breast selfexamwas reported poorly, and there were no significant differences among study sample about. The study revealedthat female students' knowledge about breast self-exam was reported poorly according to their age, marital status,and economic status.The study recommended to emphasizing to curriculum of Medical Technical Institute and should be included breastcancer knowledge and prevention, and Implementation of health education program for female students to raisebreast cancer knowledge and awareness among female students